THE IMPACT OF CANCEL CULTURE ON KAROL CONKÁ CAREER - Guarieiro, Carolina; Brenol, Marlise Viegas (Brazilian Creative Industries Journal, 2022)
This paper analyzes the impact of the cancel culture on Karol Conká’s career after participating at brazilian´s TV Globo show called Big Brother Brasil in 2021. Conká was invited to participate as a celebrity and social media influencer to join the reality show and compete for the money prize with non-celebrities. Considering the visibility that the program provides to participants and audience, the research proposes a case study on the transgressions that caused the cancellation of the artist during the period of confinement in the house and the strategies used to reconstruct her public image. This work at Social Communication main field of studies aimed to reference as theoretical concepts digital social media, visibility and digital influencers, to trace a path to the functioning of social networks dynamics. Karol Conká is a justified case study because she was eliminated with the highest rejection rate at Big Brother Brother´s history. The conflicts she was involved in during the show resulted in a loss of thousands followers on Instagram and brought important consequences for her career. As a result, the case study shows that the strategy of silence followed by mental balance narrative was well succeeded to recover audience empathy.